APLIKASI PUPUK KANDANG KAMBING PADA EMPAT VARIETAS PADI DI KABUPATEN REJANG LEBONG MELALUI SISTEM AEROBIC RICE - Kiky Nurfitri Sari; I Lisa Sridanti (University of Prof. Dr. Hazairin, SH, 2019)
The limitations of paddy fields can be overcome by the use of dry land through the application of the Aerobic Rice system. To increase rice production, the application of organic fertilizer is used as organic material that can improve the characteristics of dry land to nutrients available to plants. This study aims to determine the dose of goat manure that can increase the growth and yield of rice plants through the application of Aerobic Rice technology so as to be able to overcome the problems faced by people in Rejang Lebong District on land productivity and rice productivity. This study used factorial Randomized Complete Design, namely varieties and doses of goat manure on the Aerobic Rice system which were repeated three times. The results showed that real interactions were shown in the nine characters growth and yield observed, namely plant height, number of leaves, number of tillers, flowering age, harvest age, panicle number, panicle length and number of pellets and number of pellets per clump. The difference in varieties is clearly indicated by the eight characters of growth and results observed, namely plant height, flowering age, harvest age, panicle length, number of pithy grains, weighted grain weight and number of pithy grains per clump. The application of goat manure doses also significantly affected twelve characters observed such as plant height, number of leaves, number of tillers, age of flowering, harvest age, number of panicles, panicle length, number of rice grains, weight of grains, number of grains per clump, grain weight per clump and weight of 100 grains.